2007
DOI: 10.1186/1471-2377-7-27
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the literature on diagnostic accuracy of SPECT in parkinsonian syndromes

Abstract: Background: Parkinson's disease (PD) is the second most common neurodegenerative disorder. One of the most widely used techniques to diagnose PD is a Single Photon Emission Computer Tomography (SPECT) scan to visualise the integrity of the dopaminergic pathways in the brain. Despite this there remains some discussion on the value of SPECT in the differential diagnosis of PD. We did a meta-analysis of all the existing literature on the diagnostic accuracy of both pre-and post-synaptic SPECT imaging in the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 68 publications
4
75
0
4
Order By: Relevance
“…These results are in accordance with one meta-analysis on the diagnostic accuracy of DaTSCAN [9] and two previously published studies on the same topic [10,34]. However, the putamen/caudate ratio is greater in APS than in PD, suggesting a more uniform dopamine depletion both in putamen and in caudate nucleus in APS patients; this result concurs with the previously discussed visual assessment.…”
Section: Datscansupporting
confidence: 82%
See 1 more Smart Citation
“…These results are in accordance with one meta-analysis on the diagnostic accuracy of DaTSCAN [9] and two previously published studies on the same topic [10,34]. However, the putamen/caudate ratio is greater in APS than in PD, suggesting a more uniform dopamine depletion both in putamen and in caudate nucleus in APS patients; this result concurs with the previously discussed visual assessment.…”
Section: Datscansupporting
confidence: 82%
“…DaTSCAN imaging has high diagnostic performance in separating patients with PD from patients with non-parkinsonian syndromes [5,6]. However, the efficacy of DaTSCAN imaging in separating PD from APS has been a matter of controversy [4,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, imaging of dopamine transporter (DAT) binding with 123 I-N-v-fluoropropyl2b-carbomethoxy-3b-(4-iodophenyl)nortropan (FP-CIT) successfully visualizes presynaptic dopaminergic degeneration of the nigrostriatal tract. This procedure allows differentiation of degenerative parkinsonism from movement disorders that are not associated with dopaminergic deficit, such as essential tremor (4,5,10). DAT imaging alone, however, does not differentiate the various types of degenerative parkinsonism (PD vs. APD) with sufficient accuracy (5,11).…”
mentioning
confidence: 99%
“…In fact, various authors have shown reduced striatal binding of D2 receptor ligands in patients with Parkinson-plus syndromes and increased binding in untreated patients with early PD [69][70][71]. Even though international guidelines recommend post-synaptic imaging to distinguish PD from Parkinson-plus syndromes [69], a recent meta-analysis on the role of SPECT in parkinsonian syndromes indicated a low level of diagnostic accuracy in differentiating between PD and Parkinson-plus syndromes [72]. Furthermore, post-synaptic dopaminergic imaging does not discriminate among Parkinson-plus syndrome subgroups.…”
Section: Movement Disordersmentioning
confidence: 99%